Korelasi Keberadaan Wisata terhadap Pertumbuhan dan Tatanan Rumah Sewa di Wilayah Pesisir - Nirmayana Nirmayana; Mimi Arifin; Fathien Azmy (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2014)
Spatial planning in Indonesia is not only referring to the mainland alone, but also including coastal and marine areas. Almost all cities in Indonesia are in coastal areas. This area is located in the coastal region can be utilized as a tourist area. Makassar City, one of the cities located in coastal areas, has tourism potential that can be developed. The advent of the tourist area itself had an influence in various fields of economy, social and environment. The construction of rental houses/inns managed by locals as tourist support facilities in the region led to the construction of Tanjung Bayang develop irregular and influence environmental pollution because it does not conform with the regulations of coastal areas. On the other hand, rental houses have a positive impact of improving the welfare of local communities. This study aimed to determine the correlation to the growth of tourism destinations and order rental homes and rental housing conditions identified as supporting facilities in the tourist area of Tanjung Bayang by using correlation analysis, comparative, spatial and quantitative descriptive. The results of this study showed that the growth of the rental house in the tourist area of Tanjung Bayang significantly influenced by the presence of factors the number of visitors that travel, trade and tourism vehicle activity. Rental houses/lodging conditions grow irregularly influenced by the number of visitors and economic conditions. The output of this study to formulate the concept of realignment directives rental house in Tanjung Bayang adjusted based on conditions that exist with government regulations regarding the arrangement of the coastal region.